COMPUTING AND CLASSIFICATION OF ACOUSTIC BACKSCATTER VALUES OF THE BOTTOM SUBSTRATE OF JAKARTA BAY USING MULTIBEAM ECHOSOUNDER - Lazuardi, Muhammad Nur Riza; Manik, Henry Munandar; Setiyadi, Johar (Universitas Mataram, 2025)
Jakarta Bay is a semi-closed water area with numerous activities that trigger sedimentation, which can disrupt navigation and construction activities in Jakarta Bay. Sediment analysis and classification are useful to provide information on sediment types to support activities and coastal management in Jakarta Bay. The multibeam echosounder is an underwater acoustic research instrument that generates depth data and seabed backscatter with wide coverage and high resolution. The backscatter values are used to determine the type and grain size of sediments through the backscatter values, which function through angular response. This study uses data from the Lattek (Practical Training) Dikspespa Hidros XXI survey conducted by the Naval Technology College (STTAL) in collaboration with the Hydro-Oceanographic Education Center of the Indonesian Navy (Pusdik Hidros TNI-AL). The instruments used include the Teledyne Reson T-50R Multibeam Echosounder and the sediment grab sampler. The acoustic multibeam data were processed using Caris and FMGT software to produce bathymetric profiles and backscatter mosaics at depths ranging from 5 to 9 meters. The backscatter intensity ranges from -40 dB to -27 dB with ten classification categories: clay, silty clay, sandy clay, sandy silt, very fine silt, fine silt, medium silt, coarse silt, sandy mud, and clayey sand. The acoustic data were linked with sediment samples to classify and determine the sediment types. The results of the sediment sample analysis were divided into empat classes based on grain size: coarse clay, coarse silt, fine sand, and very fine sand.